The Strategic Role of Laboratory Management in Improving Quality of Science Learning in Elementary Schools - Saraturahmiyati; Junaidin (Mataram University, 2026)
Laboratory management is a fundamental component in the effective and quality implementation of science learning in elementary schools. This study aims to systematically examine the strategic role of laboratory management in improving the quality of science learning in elementary schools through a literature review approach. The method used is a systematic literature review of 35 scientific articles published between 2015 and 2024 from various reputable national and international journals. The results of the study indicate that good laboratory management encompasses four main dimensions: (1) management of laboratory facilities and infrastructure, (2) occupational health and safety management, (3) laboratory administration management, and (4) competency development of teachers and laboratory staff. These four dimensions have been proven to significantly contribute to improving the quality of science learning, as indicated by increased student learning motivation, scientific thinking skills, and learning outcomes. This study recommends the need for systematic policies from educational units and local governments in strengthening the governance of elementary school laboratories as a strategic effort to improve the quality of science education.